CULTURAL AND ISLAMIC VALUES IN RELATION WITH DEATH - Assous, Anissa Brighet (European Scientific Journal, ESJ, 2013)
This paper is based on my observations of Algerians’ common reactions to tragic experiences of death and mourning, the field, and information taken from various written sources. My approach is not based on contrasting Arab society with the West. Yet, I am not focusing on the Muslim world as a whole where various traditions, cultures and sects present different questions and complexities. Rather, my choice has been to write about death in the Arab and Sunni world in general and, the Algerian society in particular, by researching in hospital institutions and collecting people’s views of death and dying. By screening Sunni religious beliefs and ancestral values and traditions, I hope to understand the behavior of Algerian people when faced with a serious crisis such as kidnapping, death and mourning.